Action of the plant-based essential oil-derived compound Taxol for improvising drought tolerance in Eucalyptus by modulating the VIT1 channel protein: a cutting-edge computational approach - Xu, Chen; Debnath, Sandip; Syed, Asad; Elgorban, Abdallah M.; Bahkali, Ali H.; Eswaramaathy, Rajalakahmanen; Verma, Meenakshi; Uddin Helal, Md Mostofa; Jian, Xing (Frontiers in Genetics, 2023)
Background: Drought poses a significant threat to the growth and survival of woody plants, especially Eucalyptus grandis, which is known for its slow and steady growth. Understanding the physiological and molecular responses of Eucalyptus grandis to abiotic stress is essential for developing strategies to improve its drought resistance. This study focuses on the potential vulnerability of Eucalyptus grandis during the initial months of root system proliferation and investigates the role of essential oil derived compound Taxol in enhancing its drought resistance. Methodology: A comprehensive analysis was performed on various aspects of Eucalyptus grandis, including morphological features, photosynthetic rates, pigment concentrations, nitrogenous components, and lipid peroxidation. Furthermore, the study examined the accumulation of soluble carbohydrates, proline, and antioxidant enzymes as part of the tree's response to drought stress. Molecular docking and molecular dynamics simulations were conducted to determine the binding affinity of Taxol, an essential oil derived from Taxus brevifolia, with the VIT1 protein in Eucalyptus grandis. Results: Eucalyptus grandis displayed remarkable resilience to drought by accumulating vast reserves of soluble carbohydrates, proline, and antioxidant enzymes. The essential oil derived compound Taxol exhibited a strong binding affinity with the VIT1 protein (-10.23 kcal/mol), suggesting its potential role in enhancing the tree's drought resistance. Conclusion: This study reveals the pivotal role of Taxol in augmenting the resilience of Eucalyptus grandis against drought stress and improving its therapeutic oil properties. Emphasizing the tree's inherent tolerance during its susceptible early stages is crucial for promoting sustainable agriculture and forestry practices. The findings underscore the importance of advanced scientific research in uncovering the concealed capabilities of robust trees like Eucalyptus grandis, as we continue our pursuit of a sustainable future.